MUSLIM AND POLITICAL RULINGS ON EMBRYO TRANSPLANTATION IN UZBEKISTAN AND ITS SPIRITUAL IMPACT ON CHILDREN - Obidova Muattarbonu Husanboy qizi (Modern American Journals, 2025)
The forthcoming work covers aspects of embryo transplantation from the standpoint of Muslim scholars, as well as the influence of the forbidden method in the process of ECO on the character of children, based on sources of Muslim law. In addition, this work examines the laws of the Republic of Uzbekistan regarding the implementation of embryo transplantation, as well as the rules of ECO according to the decree of the Ministry of Health of Uzbekistan.
Keywords: ECO, embryo transplantation, fatwas, decrees, edict, law, donor, recipient, patient, artificial insemination.